Quantitative MR Imaging of the Electric Properties and Local SAR based on Improved RF Transmit Field Mapping - Voigt, Tobias (Karlsruhe transactions on biomedical engineering / Ed.: Universität Karlsruhe (TH) / Institute of Biomedical Engineering, 2011)
This work presents three new quantitative methods for magnetic resonance imaging. A method for simultaneous mapping of B1 and T1 (MTM) is developed and validated. Electric Properties Tomography (EPT), a method for quantitative imaging of dielectric properties of tissue, is presented. Based on EPT, separate (phase-based) conductivity and (amplitude-based) permittivity measurements are introduced. Finally, a B1-based method for patient-specific local SAR measurements is presented.